Gefühle. Quellen der Lebendigkeit - Bennent-Vahle, Heidemarie (B@belonline, 2023)
The essay sheds light on the importance of emotions in human life. Different emotional phenomena are identified – bodily sensations, atmospheres, moods and emotions – with special emphasis on the area of ​​emotions. Emotions are pointedly directed towards specific objects or events. They contain cognitive elements, such as desires, beliefs, fact based or value judgments, which are connected with an intensive corporeal experience and thus prove to be deeply anchored in the personality. In addition, some general structural features of emotional experience are shown, which are shaped in different ways culturally and socially as well as individually and biographically. Based on this the ambivalence of emotional experience and the difficulties of understanding others are discussed. In view of a forward-looking philosophical practice that is about self-formation and sympathetic understanding, the necessity for critical self-distancing combined with the cultivation of compassion comes into focus.